Orthogonal Regulatory Circuits for Escherichia coli Based on the γ-Butyrolactone System of Streptomyces coelicolor - Marc Biarnes-Carrera (2019)
© 2018 American Chemical Society. Chemically inducible transcription factors are widely used to control gene expression of synthetic devices. The bacterial quorum sensing system is a popular tool to achieve such control. However, different quorum sensing systems have been found to cross-talk, both between themselves and with the hosts of these devices, and they are leaky by nature. Here we evaluate the potential use of the γ-butyrolactone system from Streptomyces coelicolor A3(2) M145 as a complementary regulatory circuit. First, two additional genes responsible for the biosynthesis of γ-butyrolactones were identified in S. coelicolor M145 and then expressed in E. coli BL21 under various experimental conditions. Second, the γ-butyrolactone receptor ScbR was optimized for expression in E. coli BL21. Finally, signal and promoter crosstalk between the γ-butyrolactone system from S. coelicolor and quorum sensing systems from Vibrio fischeri and Pseudomonas aeruginosa was evaluated. The results show that the γ-butyrolactone system does not crosstalk with the quorum sensing systems and can be used to generate orthogonal synthetic circuits.